2016
DOI: 10.1108/pijpsm-03-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Law enforcement agencies’ participation in the military surplus equipment program

Abstract: Purpose The police response to the protests in Ferguson, Missouri refocused attention on law enforcement agencies’ participation in the military surplus equipment program, or 1,033 Program. Given the extensive media coverage, particularly regarding the acquisition of military vehicles and weapons, it is important to empirically investigate the 1,033 Program. The paper aims to discuss these issues. Design/methodology/approach Survey data were collected from 1,205 law enforcement regarding 1,033 Program partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The 1033 program may be used by resource-poor agencies to acquire coveted equipment, including MRAPs (Johnson & Hansen, 2016, p. 800). We therefore expect higher rates of MRAP acquisition among LEAs with smaller budgets.…”
Section: Police Militarizationmentioning
confidence: 99%
“…The 1033 program may be used by resource-poor agencies to acquire coveted equipment, including MRAPs (Johnson & Hansen, 2016, p. 800). We therefore expect higher rates of MRAP acquisition among LEAs with smaller budgets.…”
Section: Police Militarizationmentioning
confidence: 99%
“…A number of scholars have started to explore the contours of the 1033 program in regard to policing. Johnson and Hansen (2016), for example, conducted a survey of law enforcement agencies to evaluate participation in the 1033 program. They found that while a majority (61%) of agencies participated in the program, acquisition of military-like equipment differed geographically and by certain agency characteristics, such as size.…”
Section: Militarization Researchmentioning
confidence: 99%
“…Here, Koepsell and Girrard (1979) argue that consolidation is often used to provide more services or to fix issues around overlap. Johnson (2000) offers more recent examples of successful small town consolidations. However, it is unclear to what extent the merger of such small forces is relevant with regards to significantly larger forces (such as those in the UK) which already have greater capacity.…”
Section: Protective Servicesmentioning
confidence: 99%